System Constrained Active Power Loss Minimization in Practical Multi-terminal HVDC Systems through GA - Faruk Yalçın; Uğur Arifoğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this paper, a novel optimal reactive power flow solution approach inmulti-terminal HVDC (High Voltage Direct Current) systems is studied. ULTCs’(under load tap changer transformers) full equivalent model for the DCconverters’ are taken into account in the proposed AC-DC power unlike thesimilar studies in the literature. Thus, the proposed study provides realaccurate results for practical AC-DC applications. Optimal reactive power flowfor minimum active power loss is provided by Genetic Algorithm (GA). For thetest of the proposed study, the IEEE 14-bus test system modified to AC-DCsystem is used in the study. The obtained test results prove that the proposed GAbased optimization method is effective to reach the global optimum point ofminimum active power loss without dropping to local minimum point throughsatisfying system constraints.